2020
DOI: 10.1039/d0ra02036b
|View full text |Cite
|
Sign up to set email alerts
|

Paeoniflorin ameliorates glycemic variability-induced oxidative stress and platelet activation in HUVECs and DM rats

Abstract: Glycemic variability (GV) plays an important role in the pathogenesis of vascular complications associated with diabetes mellitus (DM).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 41 publications
0
3
0
Order By: Relevance
“…Lidocaine and gentamicin were administered once daily for 3 d. Seventeen days later, the ovariectomized mice were randomly divided into three groups: control, PF 1 mg/kg, and PF 10 mg/kg, and then ear-punched to distinguish individual mice. A dose of PF was decided by referring to current research focused on the treatment of T2D with PF [ [20] , [21] , [22] ]. Subcutaneous injections of the sample were started on the mice once daily for 19 d.…”
Section: Methodsmentioning
confidence: 99%
“…Lidocaine and gentamicin were administered once daily for 3 d. Seventeen days later, the ovariectomized mice were randomly divided into three groups: control, PF 1 mg/kg, and PF 10 mg/kg, and then ear-punched to distinguish individual mice. A dose of PF was decided by referring to current research focused on the treatment of T2D with PF [ [20] , [21] , [22] ]. Subcutaneous injections of the sample were started on the mice once daily for 19 d.…”
Section: Methodsmentioning
confidence: 99%
“…Basili et al [105] found that acute glucose fluctuations strongly correlated with urinary excretion of 8-iso-PGF2α, but no relationship was observed when urinary 8-iso-PGF2α excretion rates were plotted against main markers of sustained hyperglycemia (HbA1c and mean daily glucose concentrations). In our previous study, we explored platelet aggregation in HUVECs exposed to different GV media and healthy platelets and found that endothelial cells intermittently incubated with high glucose showed a more relevant increase in maximum platelet aggregation rate than the increase observed in the stable high-glucose condition [106].…”
Section: Platelet Hyperactivation In Gv-induced Dmassociated Complica...mentioning
confidence: 99%
“…Mechanistically, PF can regulate the function of immune cells and endothelial cells (ECS), reduce the production of inflammatory mediators, and restore abnormal signal transduction [9]. PF has shown notable efficacy in treating rheumatoid arthritis, psoriasis, systemic lupus erythematosus, and diabetes [10][11][12][13].Importantly, PF has been reported to inhibit high glucose-induced macrophage activation and renal inflammation [14], ameliorate glycemic variability-induced oxidative stress [15], and improve the renal biochemical and pathological damage [16]. Although the existing evidence shows that PF has a therapeutic effect on DN, its potential mechanism of action has not been fully clarified.…”
Section: Introductionmentioning
confidence: 99%